Structural Analysis of Beams in One of the Health Service Buildings in Pemalang - Rahmawati, Sally; Laksana, Muhamad Riki Dinda; Adiwibowo, Riko; Sumarman, Sumarman (Journal of Business Social and Technology, 2025)
To achieve a quality building in terms of safety, comfort, and cost efficiency, it is necessary to plan and calculate the building structure in accordance with the Indonesian National Standard (SNI) in order to fulfil the applicable construction requirements. Based on optimal safety and service criteria, the planning process must comply with SNI 1727-2019, and building structure planning must follow SNI 2847-2020 regarding reinforced concrete, as the latest regulation. The structure was analysed using ETABS software, with concrete as the material for beams, columns, and floor slabs, and concrete deck for the roof structure. The results of this process include analysis and structural design drawings for Harapan Sehat hospital Pemalang.